CCL23 in Balancing the Act of Endoplasmic Reticulum Stress and Antitumor Immunity in Hepatocellular Carcinoma - Karan, Dev (Frontiers in Oncology, 2021)
Endoplasmic reticulum (ER) stress is a cellular process in response to stress stimuli in protecting functional activities. However, sustained hyperactive ER stress influences tumor growth and development. Hepatocytes are enriched with ER and highly susceptible to ER perturbations and stress, which contribute to immunosuppression and the development of aggressive and drug-resistant hepatocellular carcinoma (HCC). ER stress-induced inflammation and tumor-derived chemokines influence the immune cell composition at the tumor site. Consequently, a decrease in the CCL23 chemokine in hepatic tumors is associated with poor survival of HCC patients and could be a mechanism hepatic tumor cells use to evade the immune system. This article describes the prospective role of CCL23 in alleviating ER stress and its impact on the HCC tumor microenvironment in promoting antitumor immunity. Moreover, approaches to reactivate CCL23 combined with immune checkpoint blockade or chemotherapy drugs may provide novel opportunities to target hepatocellular carcinoma.